Accelerometric Gait Analysis Devices in Children—Will They Accept Them? Results From the AVAPed Study - Wiedmann, Isabella; Grassi, Marcello; Duran, Ibrahim; Lavrador, Ricardo; Alberg, Evelyn; Daumer, Martin; Schoenau, Eckhard; Rittweger, Jörn (Frontiers in Pediatrics, 2021)
Aims Assessment of the children’s acceptance to wear a 3D-accelerometer which is attached to the waist under real-world conditions, and also to compare gait speed during supervised testing with the non-supervised gait speed in every-day life. Methods: In a controlled observational, cross sectional study thirty subjects with cerebral palsy (CP), classified with the Gross Motor Function Classification System (GMFCS) Level I&II and 30 healthy control children (Ctrl), aged 3-12, were asked perform a 1-minute-walking test (1mwt) under laboratory conditions, and to the wear an accelerometric device for 7 days at home (1WHM). Acceptance was measured via wearing time and a questionnaire. Subjects rated restrictions in their daily living and wearing comfort. Under laboratory conditions a mobile perambulator had been used as “gold standard“ to evaluate the validity of the accelerometric device for children. Results: Generally, acceptance was good in terms of wearing time and reported comfort. There was a difference of approximately one hour in the daily wearing time between groups (Ctrl 10.8 ± 3.6 hours, CP 9.9 ± 3.8 hours), but no significant group differences in reported restriction of activity of daily living and comfort of wearing (0.9 and pt= 0.7, respectively). Under laboratory conditions, Ctrl walked faster in the 1mwt than CP (Ctrl 1.72 ± 0.29 m/s, CP 1.48 ± 0.41 m/s, p=0.018). Similarly, a formally statistically significant difference was found also within groups comparing real-world walking speed and laboratory walking speed (CP: 1mwt 1.48 ±0.41 m/s, 1WHM 0.89 ± 0.09 m/s, p=0.012; Ctrl: 1mwt1.72 ± 0.29, 1WHM 0.97 ± 0.06, p<0.001). Conclusion: 3D-accelerometry is well accepted in paediatric rehabilitation patients. By assessing children in a non-laboratory environment, we were able to receive additional information about real world activity of CP compared with healthy children.